Crystal Guava (Psidium guajava L. “Crystal”): Evaluation of In Vitro Antioxidant Capacities and Phytochemical Content - Rika Hartati; Hashifah I. Nadifan; Irda Fidrianny (The Scientific World Journal)
Free radicals can cause many diseases, such as cancer. Antioxidant is a compound that could scavenge free radicals. One of the natural antioxidants is guava. The goals of this research were to investigate the antioxidant activity of leaves and fruit of crystal guava by determining the value of the Antioxidant Activity Index (AAI) using DPPH, CUPRAC, and FRAP; evaluate the total phenolic content (TPC) and total flavonoid content (TFC); analyse the correlation between the TPC and TFC with AAI DPPH, CUPRAC, and FRAP, and analyse the correlation between the 3 methods. Extraction was performed by the reflux method using n-hexane, ethyl acetate, and ethanol. Determination of AAI DPPH, CUPRAC, FRAP, the TPC, and the TFC was performed by UV-visible spectrophotometry. The correlation of the TPC and TFC with AAI DPPH, CUPRAC, and FRAP and, also, the correlation of the 3 methods were investigated by Pearson’s method. The antioxidant activity of leaves and fruit extracts of crystal guava showed AAI DPPH in the range of 0.33–56.46, CUPRAC 0.20–7.31, and FRAP 1.65–59.89. The highest TPC was given by ethanol leaf extracts (49.55 ± 1.45 g GAE/100 g), while the highest TFC was for n-hexane leaf extracts (9.68 ± 0.210 g QE/100 g). The TPC of leaves extract had a significantly positive correlation with AAI DPPH, CUPRAC, and FRAP. AAI DPPH, AAI CUPRAC, and AAI FRAP of leaves and fruit extract of crystal guava showed a significantly positive correlation. In general, leaves extract had strong antioxidant activity by the three methods. For the highest antioxidant activity, ethanol was the best solvent for extraction leaves and ethyl acetate for extraction fruit of crystal guava. The TPC in leaves extract contributed to the antioxidant activity by DPPH, CUPRAC, and FRAP methods. The Antioxidant activity of leaves and fruit extracts of crystal guava was linear by the three methods.